Factors that influence customers' decision to choose islamic hire purchase facility (aitab): A case study in Segamat, Johor / Muhammad Ali Imran Topan - Topan, Muhammad Ali Imran (Faculty of Business and Management, 2019)
Since Malaysia using dual financial system, it has conventional and Islamic facility in almost every aspect of financing for example home, personal and car financing. Islamic hire purchase facility has become one of the most common financing facility for car financing. Islamic hire purchase is a combination of ijarah contract, which mean to lease, hire or rent and sale and buy contract. The combination of both contract also widely known as (AlTAB). The purpose of this research is to find out the factors that influence customer decision in choosing Al TAB. Previous research conducted also focus in the area which either household with high-income per capita or lowincome per capita. By conducting this research in developing district like Segamat, it will give new insight for Islamic banking sector to identify the factors contribute towards customer decision in choosing Islamic hire purchase. The dependent variable in this study is customer decision to choose Islamic hire purchase (AITAB). This is to identify the choices of Islamic hire purchase in Segamat. Independent variables in the study is religious obligation, pricing of product, social influence, level of awareness and service quality This research will present primary data collection from the customer of Islamic bank. 100 questionnaires will be distribute to respondent using convenient sampling method.